Positive Psychology in the Military - Annen, Hubert (Studies in Military Psychology and Pedagogy, 2023)
Given that VUCA (volatility, uncertainty, complexity, and ambiguity) is a reality on the world stage, specifically military forces must regularly grap-ple with such situations and deal with potentially harmful consequences. These serving members must be able to cope effectively with the inevita-ble stressors associated with demanding circumstances or suffer signifi-cant physical and psychological consequences. Twenty-three scholars from eight countries provide well-reasoned and empirically sound guidance on best navigating these inevitable and pervasive uncertainties. Although there are no universal solutions, the advice presented in this volume offers hope and wisdom to allow our serving members to emerge victorious despite excessive pressures and challenges.